First report of Candida auris in Peru - Yagui-Moscoso, Martín (2021)
Candida auris is an emerging fungus that has gained great relevance as a global public health problem in a short time. The presence of Candida auris in 3 adult patients admitted to a national hospital of high complexity in the last quarter of 2020 in the midst of the COVID-19 pandemic is reported for the first time in Peru. The patients were hospitalized in the ICU, however, this germ was isolated in only 2 patients while they were hospitalized in the ICU. The patients had various comorbidities and long hospitalization times from admission to having their first culture positive for C. auris. All patients acquired a bacterial nosocomial infection at some point during their hospitalization and received broad-spectrum antibiotics. All isolates were resistant to Fluconazole. The hospital's infection control team reinforced containment measures and the Ministry of Health issued an epidemiological alert.